Bulletin of WHO Vol. 91 No. 03 2013. - Organization, World Health (World Health Organization, 2013)
The Bulletin of the World Health Organization is an international journal of public health with a special focus on developing countries. Since it was first published in 1948 the Bulletin has become one of the world's leading public health journals. As the flagship periodical of the World Health Organization (WHO) the Bulletin draws on WHO experts as editorial advisers reviewers and authors as well as on external collaborators. In this month's issue:The sound of silence: missing the opportunity to save lives at birth; Global health diplomacy: five years on; Landmines and explosive remnants of w.